Bioinformatics Tools for Detection and Clinical Interpretation of Genomic Variations - Samadikuchaksaraei, Ali; Seifi, Morteza (IntechOpen, 2019)
Genomic variations and phenotypic diversity are closely linked and form the underlying mechanism for development of many human diseases. This book addresses the methods of detection, analysis, and interpretation of genomic variations in clinically relevant scenarios. If your research or clinical practice involves handling of genomic sequencing data, this book is for you. Topics covered include: methods for identifying genetic diversity, the workflow for analyzing whole exome and whole genome sequencing data, local ancestry deconvolution models, the value of molecular patterns and pattern biomarkers in cancer diagnosis and prognosis, and genotyping and profiling resistance-associated variants of hepatitis C. If your research or clinical practice involves handling of genomic sequencing data, this book is for you.